Child participation in collision sports and football: what influences parental decisions? - Hibshman, N.; Yengo-Kahn, A.; Wiseman, A.; Kelly, P. D.; Wu, J.; Monk, S.; Harris, G.; Gannon, S.; Shannon, C.; Bonfield, C. M. (The Physician and Sportsmedicine, 2022)
Objective Sport participation promotes health benefits for children. Current media and scientific coverage of sport-related head injury may influence a parent`s decision on sports participation. Physicians must understand what influences these decisions to effectively counsel patients and families. This study sought to better understand and quantify the parental decisions to allow/disallow collision sports, including football participation.